Distributed Workflow Management with Smart Contracts - Taneli Hukkinen; Juri Mattila; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2017)
This report documents a blockchain application developed for the real estate sector. The application enables distributed workflow management in a complicated transaction process: the selling of a share of stocks in a housing corporation. As its core element, the application utilizes Ethereum-based smart contracts to facilitate the interaction of various parties involved, as well as the Interplanetary File System (IPFS) to combine data from a number of separate information pools. The motive for this application has been to understand the process of developing blockchain applications with industrial partners. Moreover, the purpose of this exercise has been to examine whether Ethereum-based smart contracts could be effectively utilized for applications in industry and finance. The application and the discussions during its development indicate that similar, market-driven workflow structures may appear in value chains where the number of parties is high and where the sources of information are numerous yet disconnected.
Keywords: L1; L8; L17; L73; L85; 330; Blockchain; Application; Distributed workflow; Real-estate; Ethereum; Smart contract; Immobilienwirtschaft; Anwendungssoftware; Workflow-Management-System; Vertragsrecht